Metabolomics: a brief introduction 2 - Salek, Reza (Henry Stewart Talks, 2018)
High mass accuracy/resolution, Nuclear Magnetic Resonance (NMR) vs. Mass Spectrometry (MS), GC-MS (gas chromatography-mass spec), LC-MS (Liquid chromatography-mass spec), Metabolite identification, Database search, Applications of metabolomics & resources